ಕೊಂಕಣಿ ಭಾಶೇಚ್ ಅಸ್ತಿತ್ವ - (:unkn) unknown (Konkani Language and Cultural Foundation, Mangaluru, 2003)
This book is about the stuidy of Konkani Language Existance
Konkani Bhashecha Astitva
Keywords: Konkani; ಕೊಂಕಣಿ ಭಾಶೇಚ್ ಅಸ್ತಿತ್ವ; Konkani Bhashecha Astitva; Linguistics; Konkani; Konkani